Sorteo de Plazas de Ingeniería en Administración para Desastres y Gestión del Riesgo - Llivi Ruilova, Danny Vicente (2023)
On June 5, 2023, the draw of Places was completed for tenth cycle students of the Engineering in Disaster Administration and Risk Management (APDGR) career, which were distributed among institutions in Guaranda, Chillanes, Samborondon; Fire Departments and Municipal GADs of the country.